Sociological Study of Harmony in Diversity: Lessons from Salatiga - Andika Dwiarta Putra; Daru Purnomo; Alvianto Wahyudi Utomo (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2019)
Salatiga is known for its diversity as there are more than 33 tribes living harmoniously together in this city. The existence of two religious-based education institutions, i.e. Universitas Kristen Satya Wacana and Institut Agama Islam Negeri Salatiga further proves the diversity of this city that already exists. Moreover, Salatiga respectively gained the predicate as the most top 10 tolerant cities in Indonesia within three years from a Non-Governmental Organization (NGO) that promotes tolerance. Based on functional-structural paradigm, society is assumed to be an organic system that has relationships among its parts to maintain the existing system. This study uses the constructivism approach with qualitative methods. The harmony established by CSOs, NGOs, the Government, and religious leaders through programs or activities is aimed to provide motivation and encouragement to the community or society so that they are able to maintain harmony amidst the diversity in Salatiga. Yet, it does not mean that there are no problems or obstacles threating this harmony such as the acts of radicalism from the groups originating from outside Salatiga. The radical groups are trying to mess the tolerance and harmony that has been established for a long time in Salatiga.